The assessment of sport development in a nation - Li, M.; Gerard, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: It is still an unanswered question of how sport development of a nation can be assessed. Collins (as cited in Houlihan & White, 2002) defines sport development as "a process whereby effective opportunities, processes, systems and structures are set up too enable and encourage people in all or particular groups and areas to take part in sport and recreation or to improve their performance to whatever level they desire" (p. 21). Not all sport development scholars embrace this perspective (Green, 2005; Green & Oakley, 2001a; 2001b). The purpose of this study was to identify the elements that could be used in assessing sport development of a nation. Sport development is conceptualized as a system that includes three components, the Inputs, the Process, and the Outputs. Each component of the system has a number of elements. The assessment of those elements and accordingly the three components will provide critical information about sport development of a nation. Methods The study utilized the Delphi technique. A panel of 12 experts was selected on a set of criteria. An online questionnaire was used to gather information from the panel. The questionnaire had three sections with each addressing one component of the sport development system. Both the Inputs component and the Process component contained 10 elements. There were 4 elements included in the Outputs component. The online questionnaire was posted on the SurveyMonkey.com. The members of the panel were directed to the web site and requested to rank the importance of each element using a four-point category scale with "1" being "Extremely Important", "2" being "Fairly Important", "3" being "No So Important", and "4" being "Not At All Important". In the second round survey, the aggregated ranking information was provided to the members of the panel who were asked to rank all the elements again. One element (i.e., "the physical education program") was added to the Inputs component and one to the Outputs component (i.e., "the size of the nation`s sports population"), respectively. Results The second round survey yielded relatively stable results. That is, small variability was observed in most of the elements. Among the 10 proposed elements in the Input component, "the availability of human resources (e.g., coaches, trainers, volunteers, etc.) in the process of sport development" received the highest ranking (X = 1.13), followed by "the funding provided by the government to support sport development" (X = 1.38). Three elements, "the number of youths who regularly participate in sport", "the number of community-based sport programs" and "the number of domestic sport competitions or events held annually" in the Process component, received the highest ranking of importance (X = 1.38). "The size of the nation's sports population" (X = 1.38) was viewed as the most important element in the Outputs component. Discussion / Conclusions The members of the panel endorsed most of the elements in the conceptualized system of sport development as reflected by their relatively similar ranking of importance provided to those included elements. The results not only confirmed a number of the areas as suggested by Australia Sports Commission (2004) in assessing sport development in a nation, but also were also in line with the perspective of the Ministry of Small Business and Economic Development in Canada (2001) which looks at sport development from the input side of the sport development process.